บันทึกประสบการณ์การจัดการเรียนรู้เชิงรุก ด้วยกิจกรรมการสัมภาษณ์ชาวจีน ในรายวิชาภาษาจีนชั้นต้น - ทองแดง ทัศน์ธนิต; ชาญชญานนท์ อัฐพร (Hatyai Academic Journal, 2017)
The Chinese Interview activity in 412-112 Basic Chinese 2 was an activity aimed to enable students to apply Chinese language and culture knowledge into real situations outside the classroom as well as to encourage students to communicate with native speakers, develop the face-to-face problem-solving skills in Chinese communication, and tighten the relationship between Thai students and Chinese people in the Pattani Campus. The result found that students could achieve the aims of this activity, even though some skills errors occurred, especially in pronunciation. Lastly, the author suggests that teachers should properly apply active learning teaching methods according to their situation. A good learning activity should be an integrated-skills activity., Teachers should concentrate more on developing students’ learning capability than feeding contents, together with building students’ motivation for learning. กิจกรรมการสัมภาษณ์ชาวจีน ในรายวิชา 412-112 ภาษาจีนชั้นต้น 2 เป็นกิจกรรมที่มุ่งหวังให้ผู้เรียนสามารถนำความรู้ด้านภาษาและวัฒนธรรมจีน ไปใช้ในสถานการณ์จริงนอกห้องเรียน และต้องการสร้างให้ผู้เรียนเกิดความกล้าในการสื่อสารกับเจ้าของภาษา เกิดทักษะการแก้ไขปัญหาเฉพาะหน้าในการสื่อสารภาษาจีน และเพื่อ เสริมสร้างความสัมพันธ์ระหว่างนักศึกษาไทย กับชาวจีนในมหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี ผลของการจัดกิจกรรม พบว่า ผู้เรียนสามารถบรรลุจุดมุ่งหมายของกิจกรรมนี้ แม้จะปรากฏปัญหาในบางทักษะ โดยเฉพาะทักษะการออกเสียง ผู้เขียนขอเสนอว่า ผู้สอนจำเป็นต้องปรับใช้การจัดการเรียนรู้เชิงรุก ให้เหมาะสมกับสภาพจริงของตนเอง กิจกรรมเสริมบทเรียนที่ดี ควรเป็นกิจกรรมเชิงบูรณาการหลายทักษะ ในขณะเดียวกัน ผู้สอนก็ควรเน้นการพัฒนาศักยภาพการเรียนรู้ของผู้เรียน มากกว่าการป้อนเนื้อหาความรู้ ควบคู่ไปกับการสร้างแรงจูงใจในการเรียนให้กับผู้เรียน